Flandern in der Belgischen Fotografie. (Köln : Belgisches Haus, 1982)
Fierlants, Edmond ; Dupont, Joseph ; Keusters, Leon ; Sacre, Edmond ; Hersleven, J. ; Spoor, Piet ; Buyle, Charles ; Dries, Antoon ; etc.
Flandern in der Belgischen Fotografie, Belgisches Haus, Köln, 23.9. - 23.10.82
boek
Keywords: België; Vlaanderen